Rola mediów społecznościowych w komunikowaniu politycznym - Posyłek, Małgorzata (Polityka i Społeczeństwo, 2020)
Starting efficient communication with a society is an indispensable element of a contemporary democratic state. Its aim comprises building and managing images of political stage participants, but first of all conducting a continuous social dialogue. An increase in media significance, mainly electronic media and a media saturation process, including satisfying the society significantly with information from mass media have caused politicians more and more often to take unconventional actions; actions aimed at election success. The development of modern technologies helped in the professionalization of election campaigns that have appeared on the Internet, adjusting tools of marketing communication to new channels of transmission. Politicians have placed great emphasis on this medium as they have noticed its power within public space and meaning in marketing actions. The process of building images of politicians has moved to highly interactive and multimedia social networks. The subject of analysis presented in this article is the course of the presidential campaign, candidates in the 2014 local election in Częstochowa on Facebook.